Digital Workflows and Material Sciences in Dental Medicine - Joda, Tim (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The trend of digitalization is an omnipresent phenomenon nowadays - in social life and in the dental community. Advancement in digital technology has fostered research into new dental materials for the use of these workflows, particularly in the field of prosthodontics and oral implantology.CAD/CAM-technology has been the game changer for the production of tooth-borne and implant-supported (monolithic) reconstructions: from optical scanning, to on-screen designing, and rapid prototyping using milling or 3D-printing. In this context, the continuous development and speedy progress in digital workflows and dental materials ensure new opportunities in dentistry.The objective of this Special Issue is to provide an update on the current knowledge with state-of-the-art theory and practical information on digital workflows to determine the uptake of technological innovations in dental materials science. In addition, emphasis is placed on identifying future research needs to manage the continuous increase in digitalization in combination with dental materials and to accomplish their clinical translation.This Special Issue welcomes all types of studies and reviews considering the perspectives of the various stakeholders with regard to digital dentistry and dental materials.